2004
DOI: 10.1152/ajpgi.00509.2003
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-2 induces intestinal adaptation in parenterally fed rats with short bowel syndrome

Abstract: Glucagon-like peptide-2 (GLP-2) is an intestinal trophic enteroendocrine peptide that is associated with intestinal adaptation following resection. Herein, we investigate the effects of GLP-2 in a total parenteral nutrition (TPN)-supported model of experimental short bowel syndrome. Juvenile Sprague-Dawley rats underwent a 90% small intestinal resection and jugular catheter insertion. Rats were randomized to three groups: enteral diet and intravenous saline infusion, TPN only, or TPN + 10 μg·kg−1·h−1 GLP-2. Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
121
4
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(139 citation statements)
references
References 60 publications
12
121
4
2
Order By: Relevance
“…This is evident through the increased expression of SGLT1 in the GLP-2 stretch group compared to the PEG stretch group. This matches previous studies where GLP-2 was shown to increase SGLT1 expression in short bowel resection model (38) and in tissue-engineered neointestine (39). Therefore, GLP-2 appears to contribute to increases of SGLT1 expression in these models of intestinal growth, regardless of the approach.…”
Section: Glp-2 Positively Affects the Multiple Functions In The Gastrsupporting
confidence: 90%
“…This is evident through the increased expression of SGLT1 in the GLP-2 stretch group compared to the PEG stretch group. This matches previous studies where GLP-2 was shown to increase SGLT1 expression in short bowel resection model (38) and in tissue-engineered neointestine (39). Therefore, GLP-2 appears to contribute to increases of SGLT1 expression in these models of intestinal growth, regardless of the approach.…”
Section: Glp-2 Positively Affects the Multiple Functions In The Gastrsupporting
confidence: 90%
“…9 This study uses a low dose of GLP-2 (100 μg/kg body weight/d) compared with similar studies in which GLP-2 was also given to animals undergoing bowel resection, with doses ranging from approximately 200 to 240 μg/kg body weight/d. 16,17 This dose was chosen based on a dose response study conducted in parenteral nutrition-fed rats as the lowest dose that would restore plasma GLP-2 concentrations to those of orally fed rats. 22 The dose was previously shown to induce adaptation in a parenteral nutrition-dependent rat model of SBS.…”
Section: Discussionmentioning
confidence: 99%
“…GLP-2 administration augments the adaptive response to massive intestinal resection in animal models receiving oral feedings alone and in SBS models using parenteral nutrition, or parenteral nutrition plus supplemental enteral nutrients. [14][15][16][17] In human studies, GLP-2 improves absorption and nutrition parameters in patients with reduced endogenous GLP-2 secretion due to massive bowel resection and SBS. 18 Clinical trials using teduglutide, a GLP-2 analogue resistant to degradation by dipeptidyl peptidase IV, have shown safety and evidence of adaptation in patients with SBS.…”
mentioning
confidence: 99%
“…Martin et al and Scott et al have demonstrated that GLP-2 administration following resection causes significant increases in a variety of morphological parameters including total and mucosal wet weights, crypt villus height, intestinal protein and DNA content, and crypt cell proliferation when compared with untreated resected animals. 108,109 Conversely, GLP-2 immunoneutralization of SBS mice causes inhibition of intestinal epithelia hyperplasia. 112 In addition GLP-2 administration enhanced the absorptive capacity of the residual bowel, increasing sucrase activity and expression of the sodium-dependent glucose cotransporter-1 cotransporter, compared with untreated resected animals that did not receive GLP-2 supplementation.…”
Section: -106mentioning
confidence: 99%